Real-world outcomes of spinal muscular atrophy treatment with onasemnogene abeparvovec in Croatia: a comprehensive case series and literature review - Lehman, Ivan; Matošević, Matija; Lamot, Lovro; Bunoza, Branka (Frontiers in Medicine, 2025)
IntroductionThe development of novel treatment options and the implementation of newborn screening programs have significantly transformed the landscape of care for patients with spinal muscular atrophy (SMA). In a relatively short span, SMA has evolved from a debilitating and fatal disorder into a treatable condition, primarily due to advancements in gene-targeted therapies. Onasemnogene abeparvovec-xioi, an adeno-associated viral vector-based gene therapy delivering a functional copy of the SMN1 gene, has shown significant efficacy in improving motor function and survival rates. In Croatia, this therapy has been integrated into routine clinical practice for several years, providing valuable real-world data on its long-term outcomes and effectiveness. The presented case study aims to document these clinical experiences, contributing to the growing body of evidence supporting the efficacy and safety of onasemnogene abeparvovec-xioi and highlighting the crucial role of early diagnosis and intervention in SMA management.MethodsWe conducted a retrospective case series analysis of five pediatric patients diagnosed with SMA type 1, treated with onasemnogene abeparvovec-xioi at a tertiary care center in Croatia. Four patients presented with hypotonia and motor developmental delay, and one was identified through newborn screening. All patients had genetically confirmed SMA, underwent CHOP-INTEND (Children’s Hospital of Philadelphia Infant Test of Neuromuscular Disorders) testing pre- and post-treatment, and were monitored for clinical response and adverse events. In addition, a systematic literature search was conducted using PubMed and Scopus databases to identify reports of pediatric SMA type 1 patients treated with onasemnogene abeparvovec. Keywords used included “onasemnogene abeparvovec” and “spinal muscular atrophy.” A total of 33 articles, describing 408 pediatric patients, were included.Case reportWe describe a series of five patients, four of which initially presented with varying degrees of hypotonia and delay in motor development, while one patient was discovered through newborn screening program. All patients received genetic confirmation of SMA, underwent Children’s Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP-INTEND) testing and received onasemnogene abeparvovec treatment. Four out of five patients achieved adequate clinical improvement as show by the increase in CHOP-INTEND score. One patient showed signs of regression and required additional care.ConclusionDespite the widespread use of novel treatment modalities that have drastically improved patient outcomes, there remains a paucity of real-world case reports documenting the care of SMA patients. This case series and accompanying literature review reinforce the efficacy and safety of onasemnogene abeparvovec in the treatment of SMA type 1, particularly when initiated early. In addition, our case series emphasize the critical role of newborn screening in identifying affected individuals before the onset of irreversible motor neuron loss as well as prompt start of treatment in all patients. We hope that our findings will contribute meaningfully to the expanding body of literature and knowledge on spinal muscular atrophy, ultimately fostering better patient care and outcomes.